2014
DOI: 10.4161/15384101.2014.949212
|View full text |Cite
|
Sign up to set email alerts
|

PML represses lung cancer metastasis by suppressing the nuclear EGFR-mediated transcriptional activation ofMMP2

Abstract: Promyelocytic leukemia protein (PML) is emerging as an important tumor suppressor. Its expression is lost during the progression of several types of cancer, including lung cancer. The EGF receptor (EGFR), a membrane-bound receptor tyrosine kinase, transduces intracellular signals responsible for cell proliferation, differentiation and migration. EGFR activity is frequently abnormally upregulated in lung adenocarcinoma (LAC) and thus is considered to be a driving oncogene for LAC. EGFR translocates into the nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 51 publications
1
18
0
Order By: Relevance
“…It has been reported that nEGFR is involved in regulating MMP2 promotera ctivity. [29] We found that 1 resulted in significant downregulationo f MMP2 expression ands ignificantly suppressed invasion in H1299c ells. NuclearE GFR has also been shown to regulate the proteins that cause tumor invasion, such as cyclin D1 and iNOS.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…It has been reported that nEGFR is involved in regulating MMP2 promotera ctivity. [29] We found that 1 resulted in significant downregulationo f MMP2 expression ands ignificantly suppressed invasion in H1299c ells. NuclearE GFR has also been shown to regulate the proteins that cause tumor invasion, such as cyclin D1 and iNOS.…”
mentioning
confidence: 61%
“…EGFR contentsa lso decreased in the nucleus after KPNB1 knockdown to levels similar to those observed after using 100 nm 1;t his is consistent with our findings from confocal microscopy.T ogether,t hese data show that 1 significantly inhibits KPNB1-mediated nucleari mport of EGFR in H1299 cells. It has been reported that nuclear EGFR binds to AT-rich sequence (ATR) in the promoter of matrix metalloprotease-2 (MMP2), [29] which is important for cancerm etastasis, [30] resultingi nt he expression of MMP2.B ecause 1 inhibits the translocation of EGFR to the nucleus, the regulation of MMP2 and the influenceo fM MP2 on invasion by 1 were examined by meanso ft he quantitative reverse-transcription polymerase chain reaction (qRT-PCR). As shown in Figure 3A,t reatment with 20 nm 1 resulted in significantly lower levels of MMP2 expression compared with that of the control value.…”
mentioning
confidence: 99%
“…The antibody against mouse WDR4 was described previously (39). Other antibodies used in this study are the expression of MMP2 and integrin β1 in certain cell types (10,49), their expression was not significantly induced by the WDR4/ PML axis in our cell system. Instead, our study suggests that the WDR4/PML axis acts through uPAR and SAA2 to influence the activity of integrin and MMPs.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, members of the RTK sub‐families are also present in the nucleus, and are referred to as ‘membrane receptor in the nucleus' or MRINs . Accumulating evidence indicates that at least 12 RTK families contain MRINs that exist either as a holoreceptor or in a truncated form with novel non‐canonical functions in transcriptional regulation, DNA damage and repair, and cell proliferation and invasion . In various cancer types, nuclear RTK expression is associated with poor prognosis .…”
Section: Introductionmentioning
confidence: 99%